Study of optical metallography nanostructured composite coatings Cr- SiO2-C after corrosion - Yar-Mukhamedova, G.S.; Atchibaev, R.A. (Хабаршы. Физика сериясы, 2018)
By optical metallography and scanning electron microscope to study the changes in the microstructure of nanostructured composite сoatings in 3% NaCl solution before and after corrosion tests. Found that for all the concentrations of the best anti-corrosion properties are nanostructured composite coatings obtained at temperatures of 333-343 K. This is explained by the fact that in the regime of high temperatures settle shiny coatings with fine-grained structure.